Long-term exposure to particulate matter on cardiovascular and respiratory diseases in low- and middle-income countries: A systematic review and meta-analysis - Guo, Juanmei; Chai, Guorong; Song, Xuping; Hui, Xu; Li, Zhihong; Feng, Xiaowen; Yang, Kehu (Frontiers in Public Health, 2023)
Background Long-term exposure to particulate matter (PM) has essential and profound effects on human health, but most current studies focus on high-income countries. Evidence of the correlations between PM and health effects in low- and middle-income countries (LMICs), especially the risk factor PM1 (particles < 1 μm in size), remains unclear. Objective To explore the effects of long-term exposure to particulate matter on the morbidity and mortality of cardiovascular and respiratory diseases in LMICs. Methods A systematic search was conducted in the PubMed, Web of Science, and Embase databases from inception to May 1, 2022. Cohort studies and case-control studies that examine the effects of PM1, PM2.5, and PM10 on the morbidity and mortality of cardiovascular and respiratory diseases in LMICs were included. Two reviewers independently selected the studies, extracted the data, and assessed the risk of bias. Outcomes were analyzed via a random effects model and are reported as the relative risk (RR) with 95% CI. Results Of the 1,978 studies that were identified, 38 met all the eligibility criteria. The studies indicated that long-term exposure to PM2.5, PM10, and PM1 was associated with cardiovascular and respiratory diseases: (1) Long-term exposure to PM2.5 was associated with an increased risk of cardiovascular morbidity (RR per 1.11 μg/m3, 95% CI: 1.05, 1.17) and mortality (RR per 1.10 μg/m3, 95% CI: 1.06, 1.14) and was significantly associated with respiratory mortality (RR 1.31, 95% CI: 1.25, 1.38) and morbidity (RR 1.08, 95% CI: 1.02, 1.04); (2) An increased risk of respiratory mortality was observed in the elderly (65+ years) (RR 1.21, 95% CI: 1.00, 1.47) with long-term exposure to PM2.5; (3) Long-term exposure to PM10 was associated with cardiovascular morbidity (RR 1.07, 95% CI 1.01, 1.13), respiratory morbidity (RR 1.43, 95% CI: 1.21, 1.69) and respiratory mortality (RR 1.28, 95% CI 1.10, 1.49); (4) A significant association between long-term exposure to PM1 and cardiovascular disease was also observed. Conclusions Long-term exposure to PM2.5, PM10 and PM1 was all related to cardiovascular and respiratory disease events. PM2.5 had a greater effect than PM10, especially on respiratory diseases, and the risk of respiratory mortality was significantly higher for LMICs than high-income countries. More studies are needed to confirm the effect of PM1 on cardiovascular and respiratory diseases.